2016
DOI: 10.1097/id.0000000000000405
|View full text |Cite
|
Sign up to set email alerts
|

Buccal Bone Thickness in the Esthetic Zone of Postmenopausal Women

Abstract: Buccal bone in the anterior esthetic zone bone is thin in all segments of the population, but significantly thinner in postmenopausal women. In this cohort, when anterior implants are planned, it is essential to make informed treatment planning decisions. Strategies are available to manage the thinner bony housing, but require further research specific to this growing consumer cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
1
14
1
2
Order By: Relevance
“…3,16 However, another study reported similar results to those of our study, finding that the buccal bone thickness of maxillary incisors increased gradually towards the apices. 17 These results show that the nature of bone thickness, whether increasing or decreasing towards the apex, has not been clearly established yet.…”
Section: Discussionmentioning
confidence: 87%
“…3,16 However, another study reported similar results to those of our study, finding that the buccal bone thickness of maxillary incisors increased gradually towards the apices. 17 These results show that the nature of bone thickness, whether increasing or decreasing towards the apex, has not been clearly established yet.…”
Section: Discussionmentioning
confidence: 87%
“…This study showed that thicker labial bone was noted in males when compared with females. A previous report showed that age may also be an influencing factor [18,24]. It is reported that the labial bone thickness at the cervical portion decreases with age [18]; similarly, significantly thinner labial bone was seen in postmenopausal women [24].…”
Section: Discussionmentioning
confidence: 99%
“…Posteriormente, Zhang et al (2016) comparou a espessura óssea vestibular de dentes na zona estética de mulheres na pré-menopausa, pós menopausa, homens jovens e mais velhos. A espessura foi medida em milímetros em pontos de referência em incisivos centrais e laterais superiores e inferiores utilizando um software.…”
Section: Resultsunclassified